2014
DOI: 10.1002/14651858.cd005087.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channel blockers for cystic fibrosis

Abstract: Editorial group: Cochrane Cystic Fibrosis and Genetic Disorders Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 4, 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Although initial studies showed some promise, beneficial effects could not be confirmed in subsequent studies 268,269 . Inhibition of sodium absorption was initially approached using amiloride, but limited clinical efficacy was demonstrated 270 . More potent and specific inhibitors with a longer half-life are currently being developed.…”
Section: Treatment Of the Basic Defectmentioning
confidence: 99%
“…Although initial studies showed some promise, beneficial effects could not be confirmed in subsequent studies 268,269 . Inhibition of sodium absorption was initially approached using amiloride, but limited clinical efficacy was demonstrated 270 . More potent and specific inhibitors with a longer half-life are currently being developed.…”
Section: Treatment Of the Basic Defectmentioning
confidence: 99%
“…At the moment, the interest in further investigating amiloride and its analogs as possible therapies for the treatment of cystic fibrosis lung disease seems to have fallen since no new data on clinical trials have been published. Furthermore, a recent survey covering four clinical trials with inhaled amiloride failed to demonstrate any beneficial effects by inhalation of sodium channel blockers [47].…”
Section: Amiloride and Its Analogs -Still A Possi-ble Therapy?mentioning
confidence: 99%
“…12,13 Three subsequent randomized control trials 14,16 failed to show any benefit of amiloride on respiratory function tests over a 6 to 12 month period (see also Cochrane review 2006). 17 It has been suggested that the lack of clinical benefit of amiloride is due to its short half-life on the airway surface because of rapid absorption. Higher potency sodium channel blockers with longer airway surface half-lives have been developed, most recently a compound called PS552.…”
Section: Therapymentioning
confidence: 99%